Annotated Checklist of Poroid Hymenochaetoid Fungi in Central Asia: Taxonomic Diversity, Ecological Roles, and Potential Distribution Patterns - Yusufjon Gafforov; Manzura Yarasheva; Xue-Wei Wang; Milena Rašeta; Yelena Rakhimova; Lyazzat Kyzmetova; Kanaim Bavlankulova; Sylvie Rapior; Jia-Jia Chen; Ewald Langer; Burkhon Munnavarov; Zafar Aslonov; et al. (Journal of Fungi)
Central Asia, located at the heart of Eurasia, is renowned for its varied climate and vertical vegetative distribution, which support diverse biomes and position it as a global biodiversity hotspot. Despite this ecological richness, Central Asia’s fungal diversity, particularly wood-inhabiting macrofungi, remains largely unexplored. This study investigates the diversity, ecological roles, and potential distribution of poroid Hymenochaetoid fungi in the region. By conducting field surveys, collecting basidiomes, and reviewing the literature and herbarium records from five Central Asian countries, we compiled a comprehensive checklist of these fungi. In total, 43 Hymenochaetoid species belonging to 18 genera were identified, with Inonotus, Phellinus, and Phylloporia being the most species-rich. Notably, Inonotus hispidus and Phellinus igniarius were found to be the most widespread species. These macrofungi play essential ecological roles as saprotrophs and pathogens of various identified host plant families, aiding in lignin degradation and exhibiting diverse enzymatic activities. For the first time, we modelled the potential distribution patterns of Hymenochaetoid fungi in Central Asia, revealing that their distribution is strongly influenced by host plant availability and temperature-related factors. The three most critical variables were host plant density, annual temperature range (Bio7), and mean temperature of the warmest quarter (Bio10). The distribution of suitable habitats is uneven, with highly suitable areas (4.52%) concentrated in the mountainous border regions between Kazakhstan, Kyrgyzstan, Tajikistan, and Uzbekistan. These results underscore the significance of specific environmental conditions for the growth and survival of Hymenochaetoid fungi in this region. Our findings highlight the urgent need for continued mycological and host plant research and expanded conservation initiatives to document and preserve macrofungal and botanical biodiversity in this under-explored area. In light of climate change, the collected mycological and botanical data provide a valuable reference for promoting forest health management globally.